Rituximab and improved nodular regenerative hyperplasia-associated non-cirrhotic liver disease in common variable immunodeficiency: a case report and literature study - Roosens, Willem; Staels, Frederik; Van Loo, Sien; Humblet-Baron, Stephanie; Meyts, Isabelle; De Samblanx, Hadewijch; Verslype, Chris; van Malenstein, Hannah; van der Merwe, Schalk; Laleman, Wim; Schrijvers, Rik (Frontiers in Immunology, 2023)
Common variable immunodeficiency (CVID) associated liver disease is an underrecognized and poorly studied non-infectious complication that lacks an established treatment. We describe a CVID patient with severe multiorgan complications, including non-cirrhotic portal hypertension secondary to nodular regenerative hyperplasia leading to diuretic-refractory ascites. Remarkably, treatment with rituximab, administered for concomitant immune thrombocytopenia, resulted in the complete and sustained resolution of portal hypertension and ascites. Our case, complemented with a literature review, suggests a beneficial effect of rituximab that warrants further research.